Komunikasi Interpersonal dan Massa Dalam Islam: Relevansi Ajaran Al-Qur'an untuk Penyiaran Islam Di Era Modern - Lutfiyah, Lujeng; Khuluq, Moh. Sahlul (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2024)
This study discusses the role of mass media in the dissemination of Islamic da’wah in the digital era, emphasizing the importance of applying the communication principles outlined in the Qur’an. In an increasingly connected world, mass media such as television, radio, and social media have become effective channels for spreading the message of Islam to a global audience. However, the main challenge is ensuring that the message conveyed remains aligned with Islamic teachings—communicative, honest, just, and full of wisdom. This research examines how the principles of Islamic communication can be applied in da’wah through digital media to build a positive image of Islam in the global world. Additionally, the study highlights the importance of maintaining ethical communication, including politeness, honesty, and accuracy in every message conveyed through media platforms. The findings indicate that, while digital media offers great opportunities for spreading da’wah, the application of appropriate communication ethics is crucial to ensuring that the da’wah is not only effective but also beneficial and fosters harmonious interfaith relations. The study recommends strengthening ethical communication guidelines for Islamic da’wah broadcasters to optimize the use of media in spreading messages of goodness and tolerance.